2017
DOI: 10.18869/acadpub.hms.23.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Girls' Self-Concept and Its Related Factors Based on Roy Adaptation Model

Abstract: The study of mental health status in high school female students in ... [18] Determinant factors of mental health based on ... [19] Study of mental health and its relationship with family welfare in pre-university students in ... [20] Mental health status of individuals fifteen years and older in ... [21] The role of self-concept mode of Roy's adaptation model on ... [22] The effect of care plan application based on Roy ... [23] The effect of nursing care plan based on "Roy's adaptation model" on physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the use of supportive-instructional measures in self-concept context related to the promotion of mental health of teenage girls seems necessary. In a study conducted by Basiri Moghadam et al, (13) to investigate self-conception and related factors in teenage girls of Gonabad, results showed that the self-concept of 53.4% of teenage girls was at a moderate level in total. It is notable that in the of majority subdivisions of the self-concept such as physical one, participants gained a low to moderate score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of supportive-instructional measures in self-concept context related to the promotion of mental health of teenage girls seems necessary. In a study conducted by Basiri Moghadam et al, (13) to investigate self-conception and related factors in teenage girls of Gonabad, results showed that the self-concept of 53.4% of teenage girls was at a moderate level in total. It is notable that in the of majority subdivisions of the self-concept such as physical one, participants gained a low to moderate score.…”
Section: Introductionmentioning
confidence: 99%
“…Positive self-concept can make the person feel selfconfidence and have security as well as survive against social deviations, whereas unstable self-concept causes personal conflicts among adolescents and decreases normal responses and leads to severe disturbances, mental disorders, suicide, and drug abuse in this period (10,11,13). Some studies show weakness in self-concept in teenage girls (13,14) that indicates the need to implement interventions in this context.…”
Section: Introductionmentioning
confidence: 99%
“…However, the coronavirus disease 2019 (COVID-19) pandemic had a broad range impact on people's physical and mental health, lifestyle and meaning in life [ 23 ] and has affected all health-related measures [ 24 , 25 ]. Restrictions imposed due to the pandemic, such as social distancing, have created a great need for telehealth methods in order to ensure the access of all healthcare clients to healthcare services [ 26 – 28 ]. Evidence also shows the increasing use of virtual methods by healthcare providers [ 24 ].…”
Section: Introductionmentioning
confidence: 99%